Telaah Geomorfologi Kerajaan Majapahit - Sani Safitri (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2015)
To examine the Majapahit kingdom requires kompleks. This approach is due at least discovered relics of the Majapahit kingdom so as to prove that historians need to examine the exact location of the aspects of historical geography research paper is to approach the position, climate and the morphology of the earth. Majapahit kingdom was an empire centered in East Java, Indonesia, which once stood from about 1293 to 1500 AD This kingdom reached its peak became imperial highway that controls a wide area in the archipelago during the reign of Hayam Wuruk, who ruled from 1350 to 1389. The result of research to make sure that the Majapahit capital surrounded by a network of flow paths wide and deep and have a way out to the west toward the Brantas. The source of water comes from rivers in the south of the capital.